The SA Heart Association Registry: time to SHARE your data - Doubell, Anton (SA Heart Journal, 2017)
The South African Heart Association Registry is aptly named the SHARE registry. Yet one of the factors contributing to low rates of participation appears to be a reluctance to share information from our practices and our departments. This reluctance is difficult to fathom as the standard of cardiology and cardiac surgery practiced in South Africa is considered to be high and perhaps more to the point, South African cardiologists and cardiac surgeons are not shy to sing the praises of our profession and the standard of cardiac services locally. We like to reminisce about people and events such as Chris Barnard and the first heart transplant performed in Cape Town and John Barlow’s description of mitral valve prolapse and rightly so. However, our proud past does not guarantee that our current practice puts us at the forefront of our profession.